374 The Effects of Zinc Sulfate on the in Vitro Feed Digestibility in White-Tailed Deer. (21st September 2022) - Thibodeaux, Reese J; Urso, Phil M; Kelley, Stanley F; Beverly, Marcy M; Stewart, Chris R
Abstract: The captive white-tailed deer industry has an estimated economic impact of $1.6 billion, annually. However, nutritional requirements for cervids are determined through research based on sheep and goats. The objective of this study was to determine the effects zinc on in vitro dry matter digestibility for white-tailed does (Odocoileus virginianus). Does (n=2) were euthanized ethically, rumens were collected, and placed into a cooler containing warm water. Rumen contents were agitated and filtered using cheesecloth while applying CO2 . The fluid was placed into four separate incubator jars with filter bags containing a 1:1 alfalfa to coastal hay blend. Zinc doses of 0.073 mg/kg/d were added to two of the jars (treatments), and the additional two jars received 0.00 mg/kg/d (control). Following 48 hours of incubation, in vitro true digestibility (IVTD) showed no significant differences (P >.05) between the control and treatment groups. Average dry matter digested in vitro was 91.87% and 95.13%; respectfully. Neutral detergent fiber (NDF) was no different (P >.05) between the two groups. The average digested NDF components for the control were 56.03% and the zinc group had a mean of 57.11%. Additionally, acid detergent fiber (ADF) did not statistically differ. The control group had an average of 74.56% for digested ADF components, and the treatment had a mean of 76.90%. No significant differences were observed in digested organic matter. The control group averaged 79.51% of digested organic matter (OM), and the treatment group averaged 79.38%. This methodology did prove to be viable and functional to evaluate microbial digestion in vitro. This study can be replicated with multiple experimental units to confirm the patterns of increased digestibility. Formal nutritional guidelines can be created to allow for more efficient feeding of deer. In turn, determining nutrient requirements for deer, reducing feed costs for operations, and continue educating the captive deer industry.